2020
DOI: 10.3390/ma13153421
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Response of Human Neutrophils to Hydrophilic and Hydrophobic Micro-Rough Titanium Surfaces

Abstract: Various treatments have been used to change both the topography and chemistry of titanium surfaces, aiming to enhance tissue response and reduce healing times of endosseous implants. Most studies to date focused on bone healing around dental implants occurring later during the healing cascade. However, the impact of the initial inflammatory response in the surgical wound site on the success and healing time of dental implants is crucial for implant integration and success, yet it is still poorly understood. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Ten studies assessed the interaction of neutrophils with titanium surfaces based on their roughness. One study identified intact cellular morphology and reduced chemiluminescence activity (respiratory burst) by neutrophils when interacting with serum coated moderately rough hydrophilic titanium surfaces compared to moderately rough hydrophobic titanium surfaces (El Kholy et al, 2020). A second study identified neutrophils interacting with rough hydrophilic titanium surfaces to produce low levels of interleukin‐1β (IL‐1β), IL‐6, IL‐12, tumor necrosis factor‐α, IL, neutrophils elastase, and myeloperoxidase with no NETs formation compared to neutrophils interacting with naive smooth and rough titanium surfaces (Abaricia et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies assessed the interaction of neutrophils with titanium surfaces based on their roughness. One study identified intact cellular morphology and reduced chemiluminescence activity (respiratory burst) by neutrophils when interacting with serum coated moderately rough hydrophilic titanium surfaces compared to moderately rough hydrophobic titanium surfaces (El Kholy et al, 2020). A second study identified neutrophils interacting with rough hydrophilic titanium surfaces to produce low levels of interleukin‐1β (IL‐1β), IL‐6, IL‐12, tumor necrosis factor‐α, IL, neutrophils elastase, and myeloperoxidase with no NETs formation compared to neutrophils interacting with naive smooth and rough titanium surfaces (Abaricia et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also identified different neutrophil morphology and NETotic responses to titanium surfaces with various roughness fields (Abaricia et al, 2020; Vitkov et al, 2015). Furthermore, researchers have investigated neutrophil interaction with implant surfaces having a combination of roughness/hydrophilicity, which may promote quicker healing time and reduced initial inflammatory response (Abaricia et al, 2020; El Kholy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, the leucocyte concentration was found to increase after surgery in the blood levels of all patients ( Table 2 ). Neutrophils, together with basophils and eosinophils, belong to polymorphonuclear leukocytes, constitute 40–65% of the white blood cell population and are hallmarks of acute inflammation [ 43 , 44 ]. Immediately following tissue injury, these cells are recruited and exert anti-microbial activity via degranulation, enzymatic release, phagocytosis of foreign substances and debris and the production of large DNA-based fiber networks called neutrophil extracellular traps [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic: # recruitment # ROS [198] Hydrophobic/cationic surfaces: " adhesion, FBGC fusion [72] (modified PET surfaces)…”
Section: Surface Wettability/ Chargementioning
confidence: 99%